Study on water quality of Port Shelter Bay, Hong Kong - Fang, Ming; Kester, Dana R.; Ning, Xiuren; Li, Yan (1998)
Recent years have seen harmful algal blooms and red tides become an increasing problem in coastal zones, killing invertebrates and wild stocks and cultured fish. As an inherent substance basis of red tides, eutrophication of coastal zone has been receiving increasing attention in both the scientific literature (Nixon, 1995) and in the activities of coastal resource management and environmental protection agencies. In 1992 an Estuarine Eutrophication Survey was initiated by ORCA (Ocean Resources Conservation and Assessment, USA), aimed at comprehensively assessing the scale and scope of nutrient enrichment and eutrophication in the National Estuarine Inventory (NOAA, 1998). Since early 1980's, investigations on coastal eutrophication have been carried out for the Bohai Sea (Zhou et al., 1983), the Changjiang Estuary and Hangzhou Bay (Ning, 1995), the Pearl River Estuary (Tan et al., 1993), Mirs Bay of Hong Kong (Binnie Consultants Limited, 1995), etc. However, no study on this topic for Ngau Mei Hoi Bay has been reported. A preliminary study on the water quality of Port Shelter Bay, Hong Kong was conducted in 1996, aimed at understanding the eutrophication status and expecting to recommend a series of follow-up activities that include additional and/or improved water-quality monitoring in this region.